Toward Islamic Psychology: Understanding of Mental Illness from Qur'anic Verses - Katimin Katimin; Zainal Abidin; Adelina Nasution; Ismail Fahmi Arrauf Nasution (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This article discusses an interpretation of the Qur’an by Abdullah Saeed using the contextual interpretation model. However, this paper will focus on how Abdullah Saeed developed the concept of the hierarchy of values inspired by Fazlur Rahman's thought, which discussed the problem hierarchy of values as general principles. However, Fazlur Rahman did not provide specific devices to develop the hierarchy of values. Abdullah Saeed developed and formulated the concept hierarchy of values into five levels, including obligatory values, fundamental values, protective values, implementational values, and instructional values. The five hierarchies of values become a complete unified frame as an effort to the contextual interpretation of the Qur’an, especially the ethico-legal verses that mostly fill the daily life of most Muslims based on the understanding of maqashid al-sharia and the concept of good deeds. This study uses a descriptive analysis method and hermeneutic analysis techniques to apply the concept hierarchy of values in the Qur’anic interpretation. The results of this paper are in the contextual interpretation of QS. Al-Hujurat verses 1-18 contain the five hierarchical levels of values that have been specifically conceived by Abdullah Saeed